Small lung lesions invisible under fluoroscopy are located accurately by three-dimensional localization technique on chest wall surface and performed bronchoscopy procedures to increase diagnostic yields. Issue 1 (December 2016) - Deng, Chaosheng; Cao, Xiaoming; Wu, Dawen; Ding, Haibo; You, Ruixiong; Chen, Qunlin; Chen, Linying; Zhang, Xin; Zhang, Qiaoxian; Wu, Yongquan
Abstract Background Nowadays, small peripheral pulmonary lesions (PPLs) are frequently detected and the prognosis of lung cancer depends on the early diagnosis. Because of the high fee and requiring specialized training, many advanced techniques are not available in many developing countries and rural districts. Methods Three sets of opaque soft copper wires visible under the fluoroscopy (Flu) in the Flu-flexible bronchoscopy (FB) group (n = 24), which determined the three planes of the lesion, were respectively placed firmly on the surface of the chest wall with adhesive tape on the chest wall. The FB tip was advanced into the bronchus toward the crosspoint of the three perpendicular planes under Flu with careful rotation of a C-arm unit. Then the specimen were harvested focusing around the crosspoint for pathologic diagnosis. The rapid on-site evaluation (ROSE) procedure was also performed. The average Flu time during FB procedures were recorded and diagnostic accuracy rates in the Flu-FB group were compared with the other group guided by radial endobronchial ultrasound (R-EBUS) (n = 23). Results The location of the core point of the lesion, whether it was visible or not under the fluoroscopy could be recognized by three-dimensional localization technique. The accuracy rates of diagnostic yields were 62.5% in the Flu-FB group, and was similar as 65.2% in the R-EBUS group (P > 0.05). However, in the Flu-FB group, there was a decreasing tendency on accurate diagnosis rates of lower lobe (LL) lesions when comparing with non-LL lesions (3/8 = 37.5% vs 12/16 = 75%, P = 0.091) while in the R-EBUS group it was similar (9/12 = 75% vs 6/11 = 54.6%, P = 0.278). In the Flu-FB group, fluoroscopy time was negatively correlated with the lesion length (r = −0.613, P = 0.001), however, there was no significant difference between the lesions invisible or not (5.83 ± 1.45 min vs 7.67 ± 2.02 min, P = 0.116) under the fluoroscopy, as well as no significant difference among SPN, mGGO and GGO (6.12 ± 2.05 min, 7.25 ± 1.33 min and 7.80 ± 2.02 min, P > 0.05). Conclusions Small PPL whether it is visible or not under fluoroscopy can be located accurately by our three-dimensional localization technique on chest wall surface and performed bronchoscopy procedures to increase diagnostic yields. It is more convenient, economical and reliable with the similar diagnostic yields than R-EBUS guided method. Trial registration Current Controlled TrialsChiCTR-DDD-16009715 . The date of registration: 3rd Nov, 2016. Retrospectively registered.